2006
DOI: 10.1152/ajpregu.00814.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein-methotrexate transport in dogfish shark (Squalus acanthias) choroid plexus

Abstract: The vertebrate choroid plexus removes potentially toxic metabolites and xenobiotics from cerebrospinal fluid (CSF) to blood for subsequent excretion in urine and bile. We used confocal microscopy and quantitative image analysis to characterize the mechanisms driving transport of the large organic anion, fluorescein-methotrexate (FL-MTX), from bath (CSF-side) to blood vessels in intact lateral choroid plexus from dogfish shark, Squalus acanthias, an evolutionarily ancient vertebrate. With 2 microM FL-MTX in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…This also appears to be the case for shark CP, since uptake was not inhibited by high concentrations of PAH or ES (2). In rat CP, TR uptake was Na ϩ -independent and insensitive to inhibition by high concentrations of PAH, 2,4-D, and cimetidine (present study).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This also appears to be the case for shark CP, since uptake was not inhibited by high concentrations of PAH or ES (2). In rat CP, TR uptake was Na ϩ -independent and insensitive to inhibition by high concentrations of PAH, 2,4-D, and cimetidine (present study).…”
Section: Discussionsupporting
confidence: 78%
“…Our recent experiments have shown that transport of FL-MTX in shark CP is under control of protein kinases, increasing when PKA is activated and decreasing when PKC is activated (2). Figure 10 shows differential effects of PKA activator on TR transport in rat and shark CP.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations